The Epistemology of Javanese Qur’anic Exegesis: A Study of Ṣāliḥ Darat’s Fayḍ al-Raḥmān - Abdul Mustaqim (Al-Jami'ah Research Centre, 2017)
This article seeks to analyse the structure of the epistemology of Fayḍ al-Raḥmān, a Javanese Qur’anic-exegetical work by Ṣāliḥ Darat, a prominent Javanese ulama in the nineteenth century. It is the only Javanese Qur’anic-exegetical work (kitāb al-tafsīr) with the Sufi-esoteric interpretation (al-tafsīr al-ṣūfi al-ishārī). Yet, there has not been research discussing its epistemology of interpretation whereas it is significant to grasp its fundamental structure of thought. Employing historical-philosophical approach, this article argues that Fayḍ al-Raḥmān’s exegesis reflect the illuminative epistemology (‘irfāni) by which Ṣāliḥ Darat does not only explain the textual meaning (al-ma‘nā al-ẓāhir) but also the esoteric meaning (al-ma‘nā al-ishārī) of the Qur’an. In Ṣāliḥ Darat’s view, the relation of the two resembles the relation between spirit and body that cannot be separated. The esoteric interpretation thus constitutes revealing inner meanings of the Qur’an. According to Ṣāliḥ Darat, the ideal interpretation is to grasp both the textual and esoteric meaning of the Qur’an. With the Sufi-esoteric interpretation, Ṣāliḥ Darat truly intends to bridge the epistemological polemics between Muslim jurists (fuqahā’) who are inclined to the textual meaning and Sufi-philosophers who are inclined to the esoteric meaning. Besides, written in Arabic-pegon script, Ṣāliḥ Darat’s Fayḍ al-Raḥmān fortifies the Javanese cultural identity in the sense that Javanese Qur’anic exegesis have equal authority as Arabic Qur’anic exegesis. This also reflects the cultural strategy to oppose the policy of the Dutch colonialism that enforced the use of Latin alphabet on behalf of bureaucracy and correspondence at the time.[Artikel ini mendiskusikan tentang struktur epistemologi tafsir Fayḍ al-Raḥmān karya Ṣāliḥ Darat. Kitab tersebut merupakan satu-satu kitab tafsir berbahasa Jawa dengan corak tafsir sufi isyari. Namun demikian, selama ini belum ada riset-riset terdahulu yang mengkaji tentang isu epistemologi tafsirnya. Padahal, dengan mengkaji epistemologinya, kita akan memahami struktur fundamental pemikirannya. Dengan pendekatan historis-filosofis, artikel ini berargumen bahwa epistemologi tafsir Fayḍ al-Raḥmān mencerminkan epistemologi ‘irfāni (illuminasi) dengan corak tafsir sufi isyari. Ketika menafsirkan al-Qur’an, Ṣāliḥ Darat tidak hanya menjelaskan dimensi makna zahir ayat, tetapi juga makna batinnya. Baginya, relasi keduanya tidak dapat dipisahkan, ibarat tubuh dan ruh. Sehingga, penafsiran al-Qur’an menjadi lebih hidup dan mendalam. Penafsiran yang ideal ialah manakala mampu menangkap kedua makna tersebut secara sinergis. Dengan corak tafsir sufi isyari, Ṣāliḥ Darat sebenarnya ingin mendamaikan konflik epistemik antara kaum fuqaha’ yang hanya berorietasi pada makna zahir dan kaum sufi yang hanya berorientasi pada makna batin. Di sisi lain, penggunaan tulisan Arab-Pegon dalam kitab tafsirnya merefleksikan peneguhan identitas kultural Jawa bahwa tafsir berbahasa Jawa memiliki otoritas yang sama dengan tafsir-tafsir yang berbahasa Arab. Hal ini juga merupakan strategi kebudayaan untuk melawan kolonialisme Belanda yang ketika itu menginstruksikan agar menggunakan tulisan laitin dalam birokrasi dan surat-menyurat.]